Culture of Three Seaweed Species in Cox’s Bazar Coast, Bangladesh (Bangladesh Journal of Zoology, 2021)
The experimental culture of 3 seaweed species, i.e. Hypnea musciformis, Enteromorpha intestinalis and Padina tetrastromatica in three locations of Cox’s Bazar coast, Bangladesh using 4×4 m horizontal coir rope net method were conducted during 2016 to 2018. Results showed that the biomass yield was highest from H. musciformis (30.23±0.40 kg fw m−1) and significantly differ from E. intestinalis (24.50±0.08 kg fw m−1) and P. tetrastromatica (10.18±0.45 kg fw m−1). The Daily Growth Rate (DGR) of H. musciformis (8.88% day−1) was also higher than the DGR of E. intestinalis (6.55% day−1) and P. tetrastromatica (6.74% day−1). Saint Martin’s Island showed higher biomass yield of seaweeds than Bakkhali and Inani due to favourable water quality. In context to physico-chemical parameters of seaweed farming, Cox's Bazar coast is suitable for seaweed cultivation, although more suitable culture areas and longer culture period yet to be identified. The findings of the present study suggest that the cultivation of H. musciformis is viable and coastal people can take up such activities as seasonal income generating activity in coastal water.Bangladesh J. Zool. 49(1): 47-56, 2021